Physiological Responses of Misai Kucing (Orthosiphon Stamineus Benth) Under Different Light Intensities - Abd Aziz, Fatma Azwani (2007)
The effect of shading on the growth, physiological parameters, biomass content and antioxidant activities of local Misai kucing, Orthosiphon stamineus was investigated. The growth of physiological parameters of O. stamineus was measured according to the position of the leaves on different node. The O. stamineus was grown in three different shading conditions that were 0% (receiving direct sunlight), 50% and 70% of direct sunlight by mean of shading. Black nylon netting commonly used in plant nursery that reduced 50% and 70% of the incident light cover the plants. Approximately 10 cm in length of O. stamineus cuttings were immersed in a jar filled with tap water to induce root formation before transferring to 10 x 12 cm polybag containing mixture of loam (Kosas-Peat) with organic compost (Amino-Q) in the ratio of 2:1. Common agronomic parameters and physiological parameters were recorded for every fortnight. Method used for determining the antioxidant activity was β-carotene bleaching method, whilst samples were extracted using an aqueous (water) and 80% methanol. Results showed that the exposure to the direct sunlight (0% shading) and 70% light reduction stunted the growth of O. stamineus. The biomass content was the highest under 50% shading treatment. Based on the observation, 50% shading was recommended for optimum growing condition for O. stamineus. It shows that 0% shading gives the highest leaf’s transpiration rate and stomatal conductance whilst chlorophyll concentration on leaf of O. stamineus was found at the highest-level under 70% shading. Comparison between leaves on node 3, 4, 5 and 6 respectively showed that the transpiration rate decreased towards the lower position. From the three shading treatments, it was found that the transpiration rate and stomatal conductance of the leaf was highest on leaf 3 whilst leaf 6 contained the highest chlorophyll concentration. The exposure to the high light intensity increased the transpiration rate and stomatal conductance and reduced the total chlorophyll of O. stamineus leaf. The result showed that the highest activities of antioxidant are on sixtieth minutes which was chosen to determine the comparison on activities of antioxidant between three different light exposure. The exposure under the 70% shading showed the highest percentage of antioxidant activities on leaf 6 (79.89%) for aqueous extract and leaf 4 (83.81%) for the organic extract.